Analyzing Unexpected Density Dependence Effects on Organizational Births in New York's Life Insurance Industry, 1842–1904 - Budros, Art (Organization Science, 1994)
Organizational ecologists argue that numbers of firms (density dependence) significantly affect industrial development. Rising numbers of firms are thought to legitimize a young industry, leading persons to launch new firms in the industry; but in a more crowded, older industry, increasing numbers of companies are expected to intensify competition, producing a decline in organizational births. Since this argument dominates ecological theory, results that challenge it must be explained. I identify six reasons for such results. Only a few of these explanations have been evaluated empirically and the ideas rarely have been assessed with respect to organizational births. Therefore, I address these explanations in order to resolve unexpected density dependence effects on foundings in New York's life insurance industry from 1842 to 1904. Measuring numbers of life insurance operators at both the state (New York) and national (U.S.) levels of analysis resolves the unexpected density dynamics in this study and produces a coherent pattern of density findings. Further, numbers of mutual savings banks and numbers of small life insurers in New York created competitive pressures in the life insurance business, leading persons to abandon carrier entrepreneurship. Entrepreneurship also suffered when the life insurance industry was dominated by a few large sellers. More generally, the evidence shows that New York was divided into two insurance submarkets and that carrier organizers reacted to legitimation and competition trends in the submarket occupied by domestic insurers. I conclude that once we consider the reasons for unexpected density dynamics, the core model of density dependence offers a cogent explanation for industrial evolution.